Partisipasi Masyarakat dalam Program Pengelolaan Sampah: Sebuah Tinjauan Kualitatif - Masrifah, Eva Berliana Lailatul; Hardjati, Susi (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
The waste problem shows the consequences of human life activities. Waste is defined as items that are no longer used, thrown away and come from human activities. Improper waste handling will have a negative impact on human health, environmental pollution and social problems. For this reason, there is a need for more effective waste management efforts through waste banks by involving the community as the main source of waste. One of them is Bintang Mangrove Waste Bank. However, in the process, the Bintang Mangrove Waste Bank faces various challenges, especially regarding commuity participation. This research aims to find out and describe how community participation is and how the principles of community participation are fulfilled in waste management activities at the Bintang Mangrove Waste Bank using the theory of participation. This research uses a qualitative descriptive research type. Data collection techniques through interviews, observation and documentation. The research results show that community participation in the Bintang Mangrove Waste Bank has fulfilled the principles of participation, namely the principles of equal partnership, transparency, equal powership, and sharing responsibility. However, there are still several things that need attention, such as the lack of activeness of waste bank customers in providing their ideas and need for regulations governing transparency in waste banks.